Natural killer cell therapy potentially enhances the antitumor effects of bevacizumab plus irinotecan in a glioblastoma mouse model - Tran, Thi-Anh-Thuy; Kim, Young-Hee; Duong, Thi-Hoang-Oanh; Thangaraj, JayaLakshmi; Chu, Tan-Huy; Jung, Shin; Kim, In-Young; Moon, Kyung-Sub; Kim, Young-Jin; Lee, Tae-Kyu; Lee, Chul Won; Yun, Hyosuk; et al. (Frontiers in Immunology, 2023)
Various combination treatments have been considered to attain the effective therapy threshold by combining independent antitumor mechanisms against the heterogeneous characteristics of tumor cells in malignant brain tumors. In this study, the natural killer (NK) cells associated with bevacizumab (Bev) plus irinotecan (Iri) against glioblastoma multiforme (GBM) were investigated. For the experimental design, NK cells were expanded and activated by K562 cells expressing the OX40 ligand and membrane-bound IL-18 and IL-21. The effects of Bev and Iri on the proliferation and NK ligand expression of GBM cells were evaluated through MTT assay and flow cytometry. The cytotoxic effects of NK cells against Bev plus Iri-treated GBM cells were also predicted via the LDH assay in vitro. The therapeutic effect of different injected NK cell routes and numbers combined with the different doses of Bev and Iri was confirmed according to tumor size and survival in the subcutaneous (s.c) and intracranial (i.c) U87 xenograft NOD/SCID IL-12Rγnull mouse model. The presence of injected-NK cells in tumors was detected using flow cytometry and immunohistochemistry ex vivo. As a result, Iri was found to affect the proliferation and NK ligand expression of GBM cells, while Bev did not cause differences in these cellular processes. However, the administration of Bev modulated Iri efficacy in the i.c U87 mouse model. NK cells significantly enhanced the cytotoxic effects against Bev plus Iri-treated GBM cells in vitro. Although the intravenous (IV) injection of NK cells in combination with Bev plus Iri significantly reduced the tumor volume in the s.c U87 mouse model, only the direct intratumorally (IT) injection of NK cells in combination with Bev plus Iri elicited delayed tumor growth in the i.c U87 mouse model. Tumor-infiltrating NK cells were detected after IV injection of NK cells in both s.c and i.c U87 mouse models. In conclusion, the potential therapeutic effect of NK cells combined with Bev plus Iri against GBM cells was limited in this study. Accordingly, further research is required to improve the accessibility and strength of NK cell function in this combination treatment.